The spatial distribution of soil organic carbon in tidal wetland soils of the continental United States. (17th August 2017) - Hinson, Audra L.; Feagin, Rusty A.; Eriksson, Marian; Najjar, Raymond G.; Herrmann, Maria; Bianchi, Thomas S.; Kemp, Michael; Hutchings, Jack A.; Crooks, Steve; Boutton, Thomas
Abstract: Tidal wetlands contain large reservoirs of carbon in their soils and can sequester carbon dioxide (CO2 ) at a greater rate per unit area than nearly any other ecosystem. The spatial distribution of this carbon influences climate and wetland policy. To assist with international accords such as the Paris Climate Agreement, national‐level assessments such as the United States (U.S.) National Greenhouse Gas Inventory, and regional, state, local, and project‐level evaluation of CO2 sequestration credits, we developed a geodatabase (CoBluCarb) and high‐resolution maps of soil organic carbon (SOC) distribution by linking National Wetlands Inventory data with the U.S. Soil Survey Geographic Database. For over 600, 000 wetlands, the total carbon stock and organic carbon density was calculated at 5‐cm vertical resolution from 0 to 300 cm of depth. Across the continental United States, there are 1, 153–1, 359 Tg of SOC in the upper 0–100 cm of soils across a total of 24 945.9 km 2 of tidal wetland area, twice as much carbon as the most recent national estimate. Approximately 75% of this carbon was found in estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. The greatest pool of SOC was found within the Atchafalaya/Vermilion Bay complex in Louisiana, containing about 10% of the U.S. total. The average density across all tidal wetlands was 0.071 g cm −3 across 0–15 cm, 0.055 g cm −3 across 0–100 cm, and 0.040 g cm −3 at the 100 cm depth. There is inherent variability between and within individual wetlands; however, we conclude that it is possible to use standardized values at a range of 0–100 cm of the soil profile, to provide first‐order quantification and to evaluate future changes in carbon stocks in response to environmental perturbations. This Tier 2‐oriented carbon stock assessment provides a scientific method that can be copied by other nations in support of international requirements. Abstract : In the tidal wetlands across the United States, there is 1, 152–1, 359 Tg of soil organic carbon (SOC), which is twice as much carbon as the most recent national estimate. The average area‐weighted carbon density is 0.040 g cm ‐3 at the 100 cm depth. Approximately 75% of the carbon is found in herbaceous estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. Standardized values can be used to provide a first‐order valuation of sequestration potential.